2020
DOI: 10.1021/acs.jmedchem.0c01232
|View full text |Cite
|
Sign up to set email alerts
|

Aryloxy Diester Phosphonamidate Prodrugs of Phosphoantigens (ProPAgens) as Potent Activators of Vγ9/Vδ2 T-Cell Immune Responses

Abstract: Vγ9/Vδ2 T-cells are activated by pyrophosphate-containing small molecules known as phosphoantigens (PAgs). The presence of the pyrophosphate group in these PAgs has limited their drug-like properties because of its instability and polar nature. In this work, we report a novel and short Grubbs olefin metathesis-mediated synthesis of methylene and difluoromethylene monophosphonate derivatives of the PAg ( E )-4-hydroxy-3-methyl-but-2-enyl pyrophosphate (HMBP) as well as their aryloxy diest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 56 publications
(159 reference statements)
3
26
0
Order By: Relevance
“…Our in vitro results showing inefficient bioactivation of 17 and 18 compared to bis-ester prodrugs of 5 contrast previous studies showing superior bioactivation of McGuigan prodrugs in target cell lines/typesepitomized by pharmacodynamic differences between tenofovir disoproxil and TAF in lymphoid cells. , Screening 17 and 18 in the NCI-60 cell line panel revealed no significant growth inhibition after a 10 μM incubation for 24 h despite seeing growth-inhibitory activity by their bis-ester counterparts (Figures , S6). With the exception of the fructose 1,6-bisphosphatase inhibitor “compound 35l” described by Dang and colleagues, all other reports investigating the McGuigan prodrug strategy have been on mono-substituted Cα phosphonates and, in these cases, efficient bioactivation was observed. ,,, Our experience with 17 and 18 further underscores the role of Cα substitution level in modulating the rate of the intramolecular nucleophilic phosphoryl substitution required to displace the phenolic promoiety (Figures ; S7). It can be reasonably concluded that inefficient bioactivation stems from the intramolecular cyclization step rather than the subsequent ring-opening hydrolysis, based on observations of efficient ring-opening with 30 and previous work by Meier and colleagues on cycloSal and cycloAmb (phosphonoamidate counterparts) prodrugs of adefovir. , …”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Our in vitro results showing inefficient bioactivation of 17 and 18 compared to bis-ester prodrugs of 5 contrast previous studies showing superior bioactivation of McGuigan prodrugs in target cell lines/typesepitomized by pharmacodynamic differences between tenofovir disoproxil and TAF in lymphoid cells. , Screening 17 and 18 in the NCI-60 cell line panel revealed no significant growth inhibition after a 10 μM incubation for 24 h despite seeing growth-inhibitory activity by their bis-ester counterparts (Figures , S6). With the exception of the fructose 1,6-bisphosphatase inhibitor “compound 35l” described by Dang and colleagues, all other reports investigating the McGuigan prodrug strategy have been on mono-substituted Cα phosphonates and, in these cases, efficient bioactivation was observed. ,,, Our experience with 17 and 18 further underscores the role of Cα substitution level in modulating the rate of the intramolecular nucleophilic phosphoryl substitution required to displace the phenolic promoiety (Figures ; S7). It can be reasonably concluded that inefficient bioactivation stems from the intramolecular cyclization step rather than the subsequent ring-opening hydrolysis, based on observations of efficient ring-opening with 30 and previous work by Meier and colleagues on cycloSal and cycloAmb (phosphonoamidate counterparts) prodrugs of adefovir. , …”
Section: Discussionmentioning
confidence: 79%
“…With the exception of the fructose 1,6-bisphosphatase inhibitor "compound 35l" described by Dang and colleagues, all other reports investigating the McGuigan prodrug strategy have been on mono-substituted Cα phosphonates and, in these cases, efficient bioactivation was observed. 38,39,63,66 Our experience with 17 and 18 further underscores the role of Cα substitution level in modulating the rate of the intramolecular nucleophilic phosphoryl substitution required to displace the phenolic promoiety (Figures 4; S7). It can be reasonably concluded that inefficient bioactivation stems from the intramolecular cyclization step rather than the subsequent ring-opening hydrolysis, based on observations of efficient ring-opening with 30 and previous work by Meier and colleagues on cycloSal and cycloAmb (phosphonoamidate counterparts) prodrugs of adefovir.…”
Section: ■ Conclusionmentioning
confidence: 83%
See 2 more Smart Citations
“…The same strategy was tested on the derivatives of the monophosphonate C-HMBP containing (i) different aryloxy groups, (ii) either glycine or l -alanine ester moieties, and (iii) a CH 2 –P or CF 2 –P bond (compounds 63 and 64 , Figure 10 ). These prodrugs are highly stable in human plasma and exhibit potent activation of Vγ9Vδ2 T-cell proliferation with EC 50 values from the mid-picomolar to the femtomolar range, thus displaying an efficiency similar to or even significantly greater than HMBPP [ 115 , 116 ].…”
Section: Mep Pathway As Immunostimulant Sourcementioning
confidence: 99%